PERAN TATA KELOLA PERUSAHAAN PADA PENGUNGKAPAN MODAL INTELEKTUAL - Totok Dewayanto (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2019)
The purpose of this study is to examine the role of corporate governance on the imposition of intellectual capital. This study uses company performance, capital structure and firm size as a control variable.The population in this study consisted of all manufacturing companies in the Indonesia Stock Exchange in the period 2015-2017. Sampling was carried out using the purposive sampling method. The total sample of this study was 381 companies.This study uses multiple regression analysis to test hypotheses. The results of this study indicate that board size, the proportion of independent commissioners, block holder ownership, and government ownership have a positive and significant effect on IC disclosure. Meanwhile, the board's tenure has no effect on IC disclosure.